Virgin coconut oil and its antimicrobial properties against pathogenic microorganisms: a review - Mohamad Nasir, Nur Ainatul Mardia; Wan Abd. Manan, Wan Nor Hayati; Shahdan, Intan Azura; Abllah, Zurainie; Jalaludin, Anil Azura (2018)
Virgin coconut oil (VCO) is the purest form of coconut oil, essentially water-clear or colourless that consists mainly of medium chain saturated fatty acids. For over many decades, the biological properties of VCO have been widely explored and investigated due to their antimicrobial potentials. The large concentration of medium chain fatty acids (MCFAs) including lauric acid (LA) and its monoglyceride form, monolaurin makes VCO effective in their mode of actions against pathogenic microorganisms. Thus, VCO could be used as a daily supplement or an alternative remedy against microbial infections. We review and discuss the current state of knowledge of VCO studies and focus on its antibacterial, antifungal, and antiviral activities aiming to unravel the underlying mechanisms of VCO inhibition of these pathogenic microorganisms.